Debris and Smear Layer Removal in Curved Root Canals: A Comparative Study of Ultrasonic and Sonic Irrigant Activation Techniques - Ronald Wigler; Yara Srour; Yuval Wilchfort; Zvi Metzger; Anda Kfir (MDPI AG, 2024)
The aim of this study was to compare the cleaning efficacy of three irrigant activation devices with a control of non-activated syringe and needle irrigation in curved root canals. Sixty human curved roots were endodontically prepared and divided into four groups (n = 15) with similar root curvature distributions. Final irrigation using 4% NaOCl was performed with a syringe and needle (30-G) alone, or with Eddy sonic powered irrigation system (polymeric tip #0.25/0.06), Endosonic ultrasonic activation (polymeric tip #0.25/0.03), or Irrisafe ultrasonic activation (stainless-steel tip, #0.25/0.00). SEM was used to evaluate cleaning efficacy, employing five-score systems for debris and smear layer. While no significant difference in debris removal was observed between Endosonic or Irrisafe activation and non-activated irrigation, Eddy sonic powered irrigation system significantly improved debris removal in the apical third of curved root canals. Smear layer removal was effective in coronal and mid-root sections for all groups but less so in the apical third. Thus, Eddy sonic powered irrigation system demonstrated higher efficacy in removing debris from the apical third of curved root canals compared with non-activated syringe and needle irrigation. However, all three irrigant activation systems exhibited no difference from the non-activated control in smear layer removal.